Semantic and Linguocultural Features of the Terms of the Wedding Ceremony - Xushvaqt Xakimovna Umurova (Research Parks Publishing LLC, 2021)
the article provides an overview of the semantic and lingvoculturological features of the terms wedding ceremony. However, the semantic features of these terms have been analyzed in depth. In addition, the lingvoculturological features of ceremonial terms are explained using examples.